An extralingual Ectomesenchymal chondromyxoid tumor with RREB1::MRTFB fusion: a rare case report of plantar fascia involvement - Yu Deng; Wei Liu; Ke Sun (Diagnostic Pathology)
Abstract Background Ectomesenchymal chondromyxoid tumor (ECT) is a rare benign intraoral tumor that almost exclusively presents as a small mass on the anterior dorsal tongue. Recently, the ras-responsive element-binding protein 1::myocardin-related transcription factor B (RREB1::MRTFB; previously known as MKL2) fusion gene has been identified in 90% of ECTs, all localized to the tongue, highlighting its genetic distinctiveness. Herein, we report a mesenchymal tumor involving the plantar fascia of the left foot in a young woman, harboring the RREB1::MRTFB fusion gene. Case presentation The tumor presented as a well-circumscribed mass. Following complete excision, no recurrence was observed at the six-month follow-up. Histological examination revealed tumor cells exhibiting mild nuclear atypia and very low mitotic activity. Immunohistochemical analysis showed diffuse positive staining for S100, glial fibrillary acidic protein (GFAP), and CD56, variable expression of smooth muscle actin, and negative staining for SOX10 and P63. Targeted RNA sequencing identified RREB1 (exon 8)–MRTFB (exon 11) fusion transcripts. Collectively, these findings suggest the possibility of a previously unreported extralingual ECT involving the plantar fascia. However, its atypical morphology and uncommon anatomical location posed significant diagnostic challenges. Conclusions We report, for the first time, a mesenchymal chondromyxoid tumor with an RREB1::MRTFB fusion gene occurring in the foot. This case expands the known distribution of ECT beyond the tongue. Accurate differential diagnosis should rely on thorough histological assessment, combined with immunohistochemical and molecular analyses.